A SURVEY OF CONSUMER SATISFACTION WITH MOBILE PAYMENT SYSTEM: AN EMPIRICAL STUDY OF A UNIVERSITY IN ZHEJIANG PROVINCE - Lin, Li-Wei; Ji, Zhu; Gang, Xuan (International Journal of Research -GRANTHAALAYAH, 2021)
Based on the extended study of online payment and settlement, we investigated interesting research on the use of online payment by students. This study mainly investigates the use of mobile payment consumers in a university in Haining, Zhejiang Province in 2020. The research object of this time is a university in Haining, Zhejiang Province. Mobile payment is very popular among young people. In this study, a college student was taken as the object of investigation, with 436 samples N, and the effective questionnaires reached 96%. The correlation was investigated through factor analysis. In recent years, mobile payment system has been more and more popular and used by consumers. Mobile payment is mainly applied to online and offline payment such as two-dimensional barcode shopping (purchased from vending machines and supermarkets), payment by public transportation (bus and subway), and game of grabbing red envelopes. In this study, Likert five-point scale was used to conduct factor analysis, and reliability and validity analysis of this action payment on consumer satisfaction was conducted. Convenience, security, credibility and consumer satisfaction brought by mobile payment system are the main research directions of this study. In the process of research design, we designed three hypothesis models, hoping to verify whether the hypothesis has causal correlation through this model.